The Devil’: Hermes and Èṣù in ancient Greek and Yoruba traditional religions (2016)
The history of human society reveals that belief in divinity or divinities has been an integral part of human life. Human beings have an inborn desire to identify with a supreme being or supernatural beings. However, religious beliefs differ from one society to another. Christianity and other monotheistic religions are startling different from other traditional religions. Notably, Èsù is the name given to Devil or Satan in the Yoruba translation of the Bible, Yoruba traditional religions, however, do not portray Èsù as the personal embodiment UÙof evil as reflected in the Yoruba translation of the Bible, but rather as a benevolent deity and one of the functionaries of Olódùmarè. Èsù is the Yoruba counterpart of the Greek god, Hermes, who holds a unique position in Greek religion. Hermes, like his Yoruba counterpart, is a god who wears many masks; he is the herald of the gods, a trickster and the guide that leads the dead soul into Hades as psychopompos- soul guide. Hermes and Èsù exhibit the highest number of similar traits in the pantheons of the ancient Greek and Yoruba gods. This paper examines the positions and attributes of Hermes and Èsù in the ancient Greek and Yoruba traditional religions in comparison with Biblical perceptions of Satan the Devil